Den kommunale klimaindsats 1990-2018: en komparativ analyse af fem danske kommuners klimaindsats i et historisk perspektiv - Stidsen, Mette (Politik, 2019)
Global organizations like the UN and the EU have been working towards mitigating climate change since the end of the 1980s. The media, the politicians and the scholars in Denmark often overlook the potential of local governments. This raises questions regarding the development in climate adaption and mitigation in Danish municipalities. What kind of initiatives does the municipalities implement? Are there conformity in the measures and if so, why? Are there variations in the local climate policy and if so, why? The analysis shows that the national and supranational legislation and agreements provide the framework for the climate action in the municipalities. The reasons for the variation of the implementation times are many: geographic and demographic factors, general trends, paradiplomacy and the desire for a green image.